Aristotelian Appeals and the Role of Candidate‐Generated Videos in Talent Assessment. (31st July 2018) - Huber, Amy; Pable, Jill
Abstract: Videos made by job candidates can be an effective means of promoting their qualifications, thus potentially helping them secure a job. However, little past research has focused on the impact of such videos on reviewers' appraisals of a prospective candidate. Using Aristotle's means of persuasion as a methodological framework, this study first identified the most sought after candidate attributes identified by hiring firms, then explored the degree to which firm representatives felt two candidate‐generated videos demonstrated these attributes. Findings suggest reviewers deemed the attributes characterised by pathos (emotional connections) as most important and found this quality to be most evident in the videos. As such, videos may provide the means to inject pathos into a job candidate's self‐promotional materials not possible in more traditional application packages. However, while such videos offer advantages over traditional candidate collateral, their potency can elicit strong and sometimes unintended reactions.